Making Windows into Men’s Souls: Ethical Perspectives on Spiritual Assessment in Nursing - Draper, Peter (Christian bioethics, 2013)
This paper explores the professional ethics of spiritual assessment by health professionals. Recent developments in the literature suggest that there is growing interest in the practice of spiritual assessment. We begin by reviewing recent publications in the nursing and wider health literature that describe generic, quantitative, and qualitative approaches to spiritual assessment. We then link these methods to specific discourses of spirituality. We suggest there are three major discourses, namely evidence-based, secularist, and critical spiritualities. We conclude our paper by outlining a number of professional-ethical implications of spiritual assessment. We explore whether the nursing mandate extends to include the more intrusive forms of spiritual assessment. We express doubt as to whether there is sufficient evidence in favor of spiritual interventions to validate the practice of spiritual assessment, and we note the tensions that exist, especially in the United Kingdom, concerning the provision of spiritual care in publicly funded health care.